Highly dispersed Pd nanoparticles within silica: Synthesis and characterization - Ofili, Ifeanyi Jimmy; Steinrück, Hans-Peter; Schwieger, Wilhelm; Ramakrishnan, Ayyappan; Dumbuya, K.; Gottfried, Michael (Applied Clay Science, 2011)
Well dispersed and homogeneously distributed Pd nanoparticles within a silica matrix were synthesized by a two stage process: (1) intercalation of palladium tetrammine ions into the layered aluminium-free silicate Na ilerite followed by (2) a self-reduction of the complex through decomposition of the tetrammine ligands by calcination at 550°C for 5h under N or air. Samples calcined in N predominantly contained nanoparticles of metallic Pd, while calcination in air led largely to the formation of PdO, as confirmed by XPS and supported by XRD and TGA. Thus, the Pd/PdO loading in the silica can be selectively tuned through this method. The intercalates were characterized by standard methods such as XRD, TGA, ICP and TEM. TGA of the intercalates indicated that the stabilization of the palladium tetrammine complex was enhanced by intercalation into Na ilerite. Based on ICP analysis, the Pd loadings in the intercalates were estimated to be about 18mass-%, which was also in agreement with the results from TGA. TEM revealed that the Pd/PdO nanoparticles were well dispersed in the silica matrix with an average particle size of approximately 8-10nm after calcination in air. © 2010 Elsevier B.V.

In-situ ultrasonic methods for monitoring the hydrothermal synthesis of LTA-type zeolite from colloidal solutions - Baser, Hasan-Hüseyin; Thangaraj, Thangaraj; Herrmann, Ralph; Ofili, Ifeanyi Jimmy; Schwieger, Wilhelm (Studies in Surface Science and Catalysis, 2007)
In the present study, we report the successful use of ultrasound device as a real-time, in situ diagnostic tool for monitoring the crystallization progress of zeolite A from homogeneous colloidal solutions with the composition 0.4 Na(2)O : 10 SiO(2) : 1.4 Al(2)O(3) : 16 (TMA)(2)O: 650 H(2)O. The results demonstrate that there exist good correlation between the crystallisation progress of zeolite A in terms of yield and the attenuated ultrasonic signal. It is also revealed that the kinetic information like activation energy of crystallisation reaction could be easily calculated from the measured ultrasonic signals data. In the studied case, activation energy of Ca. 30 kJ/mol was obtained.

Thermal decomposition, gas phase hydration and liquid phase reconstruction in the system Mg/Al hydrotalcite/mixed oxide: A comparative study - Mokhtar, M.; Inayat, Alexandra; Ofili, Ifeanyi Jimmy; Schwieger, Wilhelm (Applied Clay Science, 2010)
The thermal decomposition of a synthetic Mg/Al hydrotalcite and the subsequent hydration of the calcined products in the presence of water vapor at 30 degrees C were studied by in situ XRD. A comparative study between the gas phase hydration and reconstruction of calcined hydrotalcite in Na(2)CO(3) solution at 25 and 70 degrees C was investigated. TG coupled to a mass spectrometer was used to study the thermal behaviour of synthetic hydrotalcite. SEM images were taken to show the layering and size of crystals. Thermal decomposition of hydrotalcite led to the formation of a dehydrated intermediate phase at 200 degrees C. followed by crystalline MgO formation at 450 degrees C. Hydration of calcined hydrotalcite in H(2)O/N(2) resulted in the formation of broad pattems of the meixnerite phase after 2 h. This phase retained its structure even after 52 h exposure to water vapor. Reconstruction of the calcined products in carbonated water at 25 and 70 degrees C resulted in intensified patterns of the hydrotalcite phase. Due to the different structural and compositional properties of the layered products obtained by different chemical reactions of the mixed oxide phase a clarification of nomenclature for all phase transforming steps is proposed. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Hydrotalcites; Hydration; Rehydration; Reconstruction; In-situ XRD